Church-Affiliated Universities' Medical Education and the Development of Modern Medical Ethics in China: An Initial Exploration of Relevant Works by Yu Fengbin and Song Guobin - LI Qiang, (Journal of Research for Christianity in China (JRCC), 2025)
While disseminating Western medical science knowledge systems, church-affiliated universities also emphasized the education of medical ethics in their curricula. The cohort of modern Chinese “Western medicine practitioners” trained within this medical education system confronted issues of “medical ethics” and “doctor-patient relations” while practicing medicine in Chinese society. This group sought to address these contextualized medical ethics challenges through the unification of professional conduct standards within their industry community. Leveraging the Shanghai Physicians' Association as their professional community, graduates of missionary universities such as Yu Fengbin and Song Guobin assumed leadership roles in this process. Integrating medical ethics taught within the missionary university system with traditional Chinese medical ethics, they sought to regulate the medical ethics of modern Chinese “Western medicine” practitioners to resolve and prevent specific problems encountered in clinical practice. Examining this effort sheds light on the relationship between missionary university medical education and the development of modern Chinese medical ethics.